Zaufanie jako komponent adaptacji społecznej osób w sytuacji uchodźczej – wybrane teoretyczne perspektywy studiów nad zjawiskiem - Bielska, Ewa (Studia Edukacyjne, 2022)
The topic of analysis is social trust treated as a component of the process of refugees’ social adaptation. Interpersonal and institutional trust is one of the main factors conditioning the quality of civic society and local environments. Their participants are not only people with formal status of citizens but also migrants and their specific group of refugees. Social trust, sense of agency and being located in the structure of social ties and networks are the factors empowering satisfactory social functioning. They are also the components of social adaptation and the subject of concern of the different disciplines of social sciences: educational studies, social psychology and social policy.